Digital Innovation and Capability to Create Competitiveness Model of Cooperatives in Bandung, Indonesia - Ratri Wahyuningtyas; Ganjar M Disastra; Risris Rismayani (Jurnal Manajemen Indonesia, 2021)
Digital innovation refers to innovations that take advantage of digital technology to obtain new results from digitalization. Currently the digital innovation process has been implemented in a competitive and cooperative setting. Cooperatives as social organizations are required to be able to follow environmental regulations by implementing digital innovation to accelerate national economic growth, reduce poverty levels, and support equitable distribution of people's income. The inability of cooperatives to adapt to meet needs and balance the era of the industrial revolution 4.0 will result in a downturn in cooperative management, such as what happened in 2017 where almost 40% of cooperatives in West Java were inactive. In digital innovation, digital capability are also needed to connect digital technology with professional digital talent. The purpose of this study is to identify and formulate a competitiveness model through digital innovation and capabilities with government support for cooperatives in Bandung. Primary data technique consists of distributing questionnaires, interviews and secondary data through literature studies. Keywords— Digital innovation; capabilities; competitiveness; cooperatives